Sustainability in polyurethanes: old hat or new strategy for future developments? - Giulio Malucelli; Alessandra Lorenzetti (npj Materials Sustainability)
Abstract Polyurethanes are facing health and environmental problems related to their chemistry, processing and end-of-life management. This review summarizes the most recent strategies within the framework of sustainability and circularity related to the use of polyurethanes with low environmental impact, focusing on the possibility of performing their synthesis by replacing fossil-based building blocks with renewable ones, designing vitrimeric polyurethanes, and managing their end-of-life through enzymatic degradation or biodegradation processes.